2019
DOI: 10.1038/s41467-019-08977-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid active zone remodeling consolidates presynaptic potentiation

Abstract: Neuronal communication across synapses relies on neurotransmitter release from presynaptic active zones (AZs) followed by postsynaptic transmitter detection. Synaptic plasticity homeostatically maintains functionality during perturbations and enables memory formation. Postsynaptic plasticity targets neurotransmitter receptors, but presynaptic mechanisms regulating the neurotransmitter release apparatus remain largely enigmatic. By studying Drosophila neuromuscular junctions (NMJs) we sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 90 publications
(132 reference statements)
7
119
0
Order By: Relevance
“…Interestingly, also in Drosophila activity-dependent modulations of the active zone of photoreceptor synapses were observed 94 . The molecular composition of the active zone is crucial for presynaptic signaling 1,95 . The molecular mechanisms of how the ribbon contributes to the darkness-induced increased recruitment of Cav1.4 and RIM2 to the active zone remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, also in Drosophila activity-dependent modulations of the active zone of photoreceptor synapses were observed 94 . The molecular composition of the active zone is crucial for presynaptic signaling 1,95 . The molecular mechanisms of how the ribbon contributes to the darkness-induced increased recruitment of Cav1.4 and RIM2 to the active zone remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…At the Drosophila NMJ, there is considerable heterogeneity in the size and intensity of the active zone scaffold BRP and other active zone components (Guerrero et al, 2005;Peled and Isacoff, 2011;Ehmann et al, 2014;Akbergenova et al, 2018;Gratz et al, 2019). Furthermore, recent studies have shown that increasing intensity and size of active zone components, including BRP, Unc13, and the Ca 2ϩ channel Cac, predict increased release probability during baseline transmission and after homeostatic plasticity (Weyhersmüller et al, 2011;Goel et al, 2017Goel et al, , 2019bLi et al, 2018a;Böhme et al, 2019;Gratz et al, 2019). We therefore considered that while the total number of BRP puncta per NMJ was increased in the overgrowth mutants, there might have been a corresponding change in the area and/or intensity of each puncta that contributed to their modulation of release probability.…”
Section: Reduced Active Zone Area In Synaptic Overgrowth Mutants Compmentioning
confidence: 99%
“…Indeed, a positive correlation between the size and intensity of active zone components and release probability has been demonstrated at the Drosophila NMJ (Guerrero et al, 2005;Peled and Isacoff, 2011;Akbergenova et al, 2018) as well as at mammalian central synapses (Murthy et al, 2001;Matz et al, 2010;Holderith et al, 2012;Glebov et al, 2017). Furthermore, BRP can be remodeled during presynaptic homeostatic potentiation to enhance release probability at active zones (Weyhersmüller et al, 2011;Goel et al, 2017Goel et al, , 2019bBöhme et al, 2019;Gratz et al, 2019). Therefore, the reduction in active zone size observed in the overgrowth mutants likely reduces release probability at individual release sites to maintain global neurotransmitter output at the NMJ, an adaptation most dramatically illustrated in endophilin mutants (Goel et al, 2019b).…”
Section: Homeostatic Scaling Of Glutamate Receptor Abundance and Actimentioning
confidence: 99%
“…In principle, a target-specific reduction in the number and/or function of anatomical release sites could explain these electrophysiological properties. In addition, recent evidence indicates that bi-directional changes in the size and nano-structure of active zone architecture at Drosophila NMJs can adjust release probability at individual active zones (Akbergenova et al, 2018; Bohme et al, 2019; Goel et al, 2019a; Gratz et al, 2019). We therefore characterized the number and intensity of individual active zones on hyper-innervated NMJs by immunostaining the central scaffold BRP and endogenously tagged CaV2.1 calcium channels [Cac sfGFP ; (Gratz et al, 2019)], defining each BRP punctum to be an active zone.…”
Section: Resultsmentioning
confidence: 99%